2022
DOI: 10.1016/j.ultsonch.2021.105884
|View full text |Cite
|
Sign up to set email alerts
|

β-Glucan from mushrooms and dates as a wall material for targeted delivery of model bioactive compound: Nutraceutical profiling and bioavailability

Abstract: Rutin was nano-encapsulated in date [En-Ru(D)] and mushroom [En-Ru(M)] β-glucan matrix to protect it from the harsh gastrointestinal environment and to enhance its bioavailability and biological activity upon digestion. The encapsulation was carried using green technology i.e., ultra-sonication. The En-Ru(D) and En-Ru (M) showed the hydrodynamic diameter of 314.04 and 482.21 nm with polydispersity index of 0.21 and 0.33. The in vitro release behaviour followed the Higuchi model. The antimicrobial activity of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The distortion of protein upon ultra-sonication may be because of the denaturation and unfolding of protein structure due to cavitation forces resulting in change of morphological properties of protein [24] . Du et al [25] reported the similar morphological change in pumpkin seed protein upon sonication.
Fig.
…”
Section: Resultsmentioning
confidence: 76%
“…The distortion of protein upon ultra-sonication may be because of the denaturation and unfolding of protein structure due to cavitation forces resulting in change of morphological properties of protein [24] . Du et al [25] reported the similar morphological change in pumpkin seed protein upon sonication.
Fig.
…”
Section: Resultsmentioning
confidence: 76%
“…Owing to the ability of bioactive compounds to stabilize via the structuring of systems that preserve their chemical, physical, and biological properties, and their release (or delivery) under desired conditions [ 59 ], microencapsulation technologies have been gaining popularity in the food industry during the last few decades. Although β-glucan is usually used as a wall agent (encapsulant) for bioactive compound encapsulation [ 60 , 61 , 62 , 63 , 64 , 65 ], this soluble fiber was employed in our study as a core material to be microencapsulated using two different techniques to improve its stability and nutritional value for scientific purposes and practical applications.…”
Section: Discussionmentioning
confidence: 99%
“…However, at pH 7.5 (simulated intestinal conditions), NT-Chl and Nano-Chl capsules exhibited a lower swelling index of 63.14% and 60.43%, respectively. This is attributed to the higher dissolution/disintegration of the apple protein in the alkaline medium followed by the release of chlorogenic acid [ 15 ]. These results are in accordance with a previous study reported by Gani et al [ 19 ] in which churpi protein was used as wall material for the encapsulation of resveratrol.…”
Section: Resultsmentioning
confidence: 99%
“…Apple seed protein nanoparticles were prepared following the method of Shah et al [ 15 ]. Briefly, apple seed protein dissolved in phosphate buffer solution (pH 7) was ultrasonicated at a frequency of 40 KHz for 25 min with a pause of 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation